Validity of E-LKPD Based on POE Learning Model on Static Fluid Material to Improve Students' Critical Thinking Skills - Dewi, Sonia Citra (Universitas Negeri Padang, 2025)
This study aims to design and test the validity of E-LKPD (Electronic Student Worksheet) based on the Predict-Observe-Explain (POE) learning model as an interactive learning medium to improve students' critical thinking skills in static fluid material. This E-LKPD was developed as an alternative teaching material that combines a constructivist approach with the use of digital technology in learning. The research method used was Research and Development (R&D) with a 4D development model, which includes the stages of define, design, develop, and disseminate. However, this study was limited to the develop stage, which focused on the validation of the E-LKPD by experts. The validation process was conducted by physics education lecturers from the University of Padang, who assessed the substance of the material, design, learning structure, and the suitability of the E-LKPD with the characteristics of the POE model. The validation results showed that the developed E-LKPD had very good quality with an overall average score of 0.90 and was categorized as valid. Thus, this POE-based E-LKPD is suitable for use as an innovative learning tool that not only supports the mastery of static fluid concepts but also develops students' critical thinking skills in the context of 21st-century learning.